Growing Grounded Theory: - Helen Scott (Grounded Theory Review: An International Journal)
In Glaser s recent book, The Grounded Theory Perspective: Its Origin and Growth (2016), Glaser writes of how he recorded and explicated the grounded theory perspective and disseminated the perspective as the grounded theory general method of research, over a period of 50 years. During this period he has monitored its use, embracing procedural developments (e.g. Nilsson, 2011; Scott, 2011), whilst vigorously defending and differentiating the grounded theory perspective from adaptions (e.g. Glaser, 1992, 2002). A scholastic endeavour of monumental proportions.